Keabsahan Perkawinan Beda Agama Ada Di Tangan Hakim? - Mudakir, Kharis (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2024)
This research explores the controversy that still occurs surrounding the Judge's approval in registering marriages between individuals of different religions, even though many religions and laws prohibit interfaith marriages. This research seeks to analyze the factors that are taken into consideration by judges in their decisions, in accordance with relevant laws and regulations in marriage law and the KHI (Compilation of Islamic Law). The research method used is qualitative, especially library research. This approach uses a normative legal approach as an analytical tool which aims to provide a comprehensive understanding of existing problems. The findings of this research highlight the important role of judges in determining the validity of interfaith marriages. Decision Number 508/Pdt.P/2022/PN JKT.SEL was granted, while Decision Number 71/Pdt.P/2017/PN Bla was rejected. The judge's interpretation of Article 2 paragraph (1) of the Marriage Law plays an important role in the validity of interfaith marriages, even though there are quite significant differences with the Compilation of Islamic Law.